2016
DOI: 10.1021/acschembio.5b01076
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific Profiling of Nascent Proteomes Using Orthogonal Enzyme-mediated Puromycin Incorporation

Abstract: Translation regulation is a fundamental component of gene expression, allowing cells to respond rapidly to a variety of stimuli in the absence of new transcription. The lack of methods for profiling nascent proteomes in distinct cell populations in heterogeneous tissues has precluded an understanding of translational regulation in physiologically relevant contexts. Here, we describe a chemical genetic method that involves orthogonal enzyme-mediated incorporation of a clickable puromycin analogue into nascent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…The data may also reflect the inherent technical limitations of using a basic SILAC approach in non-dividing cells, since it was difficult to identify a time point allowing sufficient labeling that also revealed clear differences between conditionally lesioned and naive cultures. Future work in such models should use methods that do not require extensive labeling or pre-incubation periods, such as recently described methods based on O-propargyl-puromycin (OPP) labeling ( Barrett et al, 2016 ; Forester et al, 2018 ), that can also be conducted in tissues and potentially also in vivo ( Terenzio et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data may also reflect the inherent technical limitations of using a basic SILAC approach in non-dividing cells, since it was difficult to identify a time point allowing sufficient labeling that also revealed clear differences between conditionally lesioned and naive cultures. Future work in such models should use methods that do not require extensive labeling or pre-incubation periods, such as recently described methods based on O-propargyl-puromycin (OPP) labeling ( Barrett et al, 2016 ; Forester et al, 2018 ), that can also be conducted in tissues and potentially also in vivo ( Terenzio et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another labeling approach that takes advantage of the cell’s native protein synthesis machinery uses a puromycin analog tag [92,93,94,95]. The puromycin analog binds the acceptor (A) site of the ribosome and is then incorporated into the nascent polypeptide chain prior to inhibition of protein synthesis.…”
Section: Proteome Labeling Methodsmentioning
confidence: 99%
“…Most of what we know about translation has been gathered from experiments either in vitro with purified protein components [54,55], in populations of lysed (dead) cells [5658], or indirectly in living cells by examining the translational end product: mature proteins [59]. These studies have revealed that translation is an energy intensive process [60] that can be divided into four key steps [61,62]: ribosome search and recruitment, initiation, nascent peptide elongation, and termination.…”
Section: Figurementioning
confidence: 99%